TacticsMore Basic Tactics
Set Warnings "-notation-overridden,-parsing,-deprecated-hint-without-locality".
From LF Require Export Poly.
The apply Tactic
Theorem silly1 : ∀ (n m : nat),
n = m →
n = m.
Proof.
intros n m eq.
n = m →
n = m.
Proof.
intros n m eq.
Here, we could finish with "rewrite → eq. reflexivity." as we
have done several times before. Alternatively, we can finish in
a single step by using the apply tactic:
apply eq. Qed.
Theorem silly2 : ∀ (n m o p : nat),
n = m →
(n = m → [n;o] = [m;p]) →
[n;o] = [m;p].
Proof.
intros n m o p eq1 eq2.
apply eq2. apply eq1. Qed.
n = m →
(n = m → [n;o] = [m;p]) →
[n;o] = [m;p].
Proof.
intros n m o p eq1 eq2.
apply eq2. apply eq1. Qed.
Theorem silly2a : ∀ (n m : nat),
(n,n) = (m,m) →
(∀ (q r : nat), (q,q) = (r,r) → [q] = [r]) →
[n] = [m].
Proof.
intros n m eq1 eq2.
apply eq2. apply eq1. Qed.
(n,n) = (m,m) →
(∀ (q r : nat), (q,q) = (r,r) → [q] = [r]) →
[n] = [m].
Proof.
intros n m eq1 eq2.
apply eq2. apply eq1. Qed.
Theorem silly3 : ∀ (n m : nat),
n = m →
m = n.
Proof.
intros n m H.
n = m →
m = n.
Proof.
intros n m H.
Here we cannot use apply directly...
Fail apply H.
but we can use the symmetry tactic, which switches the left
and right sides of an equality in the goal.
symmetry. apply H. Qed.
The apply with Tactic
Example trans_eq_example : ∀ (a b c d e f : nat),
[a;b] = [c;d] →
[c;d] = [e;f] →
[a;b] = [e;f].
Proof.
intros a b c d e f eq1 eq2.
rewrite → eq1. rewrite → eq2. reflexivity. Qed.
[a;b] = [c;d] →
[c;d] = [e;f] →
[a;b] = [e;f].
Proof.
intros a b c d e f eq1 eq2.
rewrite → eq1. rewrite → eq2. reflexivity. Qed.
Since this is a common pattern, we might like to pull it out as a lemma that records, once and for all, the fact that equality is transitive.
Theorem trans_eq : ∀ (X:Type) (n m o : X),
n = m → m = o → n = o.
Proof.
intros X n m o eq1 eq2. rewrite → eq1. rewrite → eq2.
reflexivity. Qed.
n = m → m = o → n = o.
Proof.
intros X n m o eq1 eq2. rewrite → eq1. rewrite → eq2.
reflexivity. Qed.
Example trans_eq_example' : ∀ (a b c d e f : nat),
[a;b] = [c;d] →
[c;d] = [e;f] →
[a;b] = [e;f].
Proof.
intros a b c d e f eq1 eq2.
[a;b] = [c;d] →
[c;d] = [e;f] →
[a;b] = [e;f].
Proof.
intros a b c d e f eq1 eq2.
Doing apply trans_eq doesn't work! But...
apply trans_eq with (m:=[c;d]).
does.
apply eq1. apply eq2. Qed.
Example trans_eq_example'' : ∀ (a b c d e f : nat),
[a;b] = [c;d] →
[c;d] = [e;f] →
[a;b] = [e;f].
Proof.
intros a b c d e f eq1 eq2.
transitivity [c;d].
apply eq1. apply eq2. Qed.
[a;b] = [c;d] →
[c;d] = [e;f] →
[a;b] = [e;f].
Proof.
intros a b c d e f eq1 eq2.
transitivity [c;d].
apply eq1. apply eq2. Qed.
The injection and discriminate Tactics
- if S n = S m then it must be that n = m
- O is not equal to S n for any n
We can prove the injectivity of S by using the pred function defined in Basics.v.
Theorem S_injective : ∀ (n m : nat),
S n = S m →
n = m.
Proof.
intros n m H1.
assert (H2: n = pred (S n)). { reflexivity. }
rewrite H2. rewrite H1. simpl. reflexivity.
Qed.
S n = S m →
n = m.
Proof.
intros n m H1.
assert (H2: n = pred (S n)). { reflexivity. }
rewrite H2. rewrite H1. simpl. reflexivity.
Qed.
Theorem S_injective' : ∀ (n m : nat),
S n = S m →
n = m.
Proof.
intros n m H.
injection H as Hnm. apply Hnm.
Qed.
S n = S m →
n = m.
Proof.
intros n m H.
injection H as Hnm. apply Hnm.
Qed.
Theorem injection_ex1 : ∀ (n m o : nat),
[n;m] = [o;o] →
n = m.
Proof.
intros n m o H.
(* WORK IN CLASS *) Admitted.
[n;m] = [o;o] →
n = m.
Proof.
intros n m o H.
(* WORK IN CLASS *) Admitted.
Theorem discriminate_ex1 : ∀ (n m : nat),
false = true →
n = m.
Proof.
intros n m contra. discriminate contra. Qed.
Theorem discriminate_ex2 : ∀ (n : nat),
S n = O →
2 + 2 = 5.
Proof.
intros n contra. discriminate contra. Qed.
false = true →
n = m.
Proof.
intros n m contra. discriminate contra. Qed.
Theorem discriminate_ex2 : ∀ (n : nat),
S n = O →
2 + 2 = 5.
Proof.
intros n contra. discriminate contra. Qed.
These examples are instances of a logical principle known as the
principle of explosion, which asserts that a contradictory
hypothesis entails anything (even manifestly false things!).
For a slightly more involved example, we can use discriminate to
make a connection between the two different notions of
equality (= and =?) on natural numbers.
Theorem eqb_0_l : ∀ n,
0 =? n = true → n = 0.
Proof.
intros n.
destruct n as [| n'] eqn:E.
- (* n = 0 *)
intros H. reflexivity.
- (* n = S n' *)
simpl.
intros H. discriminate H.
Qed.
0 =? n = true → n = 0.
Proof.
intros n.
destruct n as [| n'] eqn:E.
- (* n = 0 *)
intros H. reflexivity.
- (* n = S n' *)
simpl.
intros H. discriminate H.
Qed.
Suppose Coq's proof state looks like
x : bool
y : bool
H : negb x = negb y
============================
y = x and we apply the tactic injection H as Hxy. What will happen?
(1) "No more subgoals."
(2) The tactic fails.
(3) Hypothesis H becomes Hxy : x = y.
(4) None of the above.
x : bool
y : bool
H : negb x = negb y
============================
y = x and we apply the tactic injection H as Hxy. What will happen?
Now suppose Coq's proof state looks like
x : nat
y : nat
H : x + 1 = y + 1
============================
y = x and we apply the tactic injection H as Hxy. What will happen?
(1) "No more subgoals."
(2) The tactic fails.
(3) Hypothesis H becomes Hxy : x = y.
(4) None of the above.
x : nat
y : nat
H : x + 1 = y + 1
============================
y = x and we apply the tactic injection H as Hxy. What will happen?
Finally, suppose Coq's proof state looks like
x : nat
y : nat
H : 1 + x = 1 + y
============================
y = x and we apply the tactic injection H as Hxy. What will happen?
(1) "No more subgoals."
(2) The tactic fails.
(3) Hypothesis H becomes Hxy : x = y.
(4) None of the above.
x : nat
y : nat
H : 1 + x = 1 + y
============================
y = x and we apply the tactic injection H as Hxy. What will happen?
The injectivity of constructors allows us to reason that ∀ (n m : nat), S n = S m → n = m. The converse of this implication is an instance of a more general fact about both constructors and functions, which we will find convenient in a few places below:
Theorem f_equal : ∀ (A B : Type) (f: A → B) (x y: A),
x = y → f x = f y.
Proof. intros A B f x y eq. rewrite eq. reflexivity. Qed.
Theorem eq_implies_succ_equal : ∀ (n m : nat),
n = m → S n = S m.
Proof. intros n m H. apply f_equal. apply H. Qed.
x = y → f x = f y.
Proof. intros A B f x y eq. rewrite eq. reflexivity. Qed.
Theorem eq_implies_succ_equal : ∀ (n m : nat),
n = m → S n = S m.
Proof. intros n m H. apply f_equal. apply H. Qed.
Or we can just use the f_equal tactic.
Theorem eq_implies_succ_equal' : ∀ (n m : nat),
n = m → S n = S m.
Proof. intros n m H. f_equal. apply H. Qed.
n = m → S n = S m.
Proof. intros n m H. f_equal. apply H. Qed.
Using Tactics on Hypotheses
Theorem S_inj : ∀ (n m : nat) (b : bool),
((S n) =? (S m)) = b →
(n =? m) = b.
Proof.
intros n m b H. simpl in H. apply H. Qed.
((S n) =? (S m)) = b →
(n =? m) = b.
Proof.
intros n m b H. simpl in H. apply H. Qed.
The ordinary apply tactic is a form of "backward reasoning": it says "We're trying to prove X and we know Y → X, so if we can prove Y we'll be done."
Theorem silly4 : ∀ (n m p q : nat),
(n = m → p = q) →
m = n →
q = p.
Proof.
intros n m p q EQ H.
symmetry in H. apply EQ in H. symmetry in H.
apply H. Qed.
(n = m → p = q) →
m = n →
q = p.
Proof.
intros n m p q EQ H.
symmetry in H. apply EQ in H. symmetry in H.
apply H. Qed.
Varying the Induction Hypothesis
Fixpoint double (n:nat) :=
match n with
| O ⇒ O
| S n' ⇒ S (S (double n'))
end.
match n with
| O ⇒ O
| S n' ⇒ S (S (double n'))
end.
Suppose we want to show that double is injective -- i.e., that it maps different arguments to different results. The way we start this proof is a little bit delicate:
Theorem double_injective_FAILED : ∀ n m,
double n = double m →
n = m.
Proof.
intros n m. induction n as [| n' IHn'].
- (* n = O *) simpl. intros eq. destruct m as [| m'] eqn:E.
+ (* m = O *) reflexivity.
+ (* m = S m' *) discriminate eq.
- (* n = S n' *) intros eq. destruct m as [| m'] eqn:E.
+ (* m = O *) discriminate eq.
+ (* m = S m' *) apply f_equal.
double n = double m →
n = m.
Proof.
intros n m. induction n as [| n' IHn'].
- (* n = O *) simpl. intros eq. destruct m as [| m'] eqn:E.
+ (* m = O *) reflexivity.
+ (* m = S m' *) discriminate eq.
- (* n = S n' *) intros eq. destruct m as [| m'] eqn:E.
+ (* m = O *) discriminate eq.
+ (* m = S m' *) apply f_equal.
At this point, the induction hypothesis (IHn') does not give us
n' = m' -- there is an extra S in the way -- so the goal is
not provable.
Abort.
A successful proof of double_injective leaves m universally quantified in the goal statement at the point where the induction tactic is invoked on n:
Theorem double_injective : ∀ n m,
double n = double m →
n = m.
Proof.
intros n. induction n as [| n' IHn'].
- (* n = O *) simpl. intros m eq. destruct m as [| m'] eqn:E.
+ (* m = O *) reflexivity.
+ (* m = S m' *) discriminate eq.
- (* n = S n' *)
intros m eq.
destruct m as [| m'] eqn:E.
+ (* m = O *)
discriminate eq.
+ (* m = S m' *)
apply f_equal.
apply IHn'. simpl in eq. injection eq as goal. apply goal. Qed.
double n = double m →
n = m.
Proof.
intros n. induction n as [| n' IHn'].
- (* n = O *) simpl. intros m eq. destruct m as [| m'] eqn:E.
+ (* m = O *) reflexivity.
+ (* m = S m' *) discriminate eq.
- (* n = S n' *)
intros m eq.
destruct m as [| m'] eqn:E.
+ (* m = O *)
discriminate eq.
+ (* m = S m' *)
apply f_equal.
apply IHn'. simpl in eq. injection eq as goal. apply goal. Qed.
The thing to take away from all this is that you need to be careful, when using induction, that you are not trying to prove something too specific: When proving a property involving two variables n and m by induction on n, it is sometimes crucial to leave m generic.
Exercise: 2 stars, standard (eqb_true)
Theorem eqb_true : ∀ n m,
n =? m = true → n = m.
Proof.
(* FILL IN HERE *) Admitted.
☐
n =? m = true → n = m.
Proof.
(* FILL IN HERE *) Admitted.
☐
The strategy of doing fewer intros before an induction to obtain a more general IH doesn't always work by itself; sometimes some rearrangement of quantified variables is needed. Suppose, for example, that we wanted to prove double_injective by induction on m instead of n.
Theorem double_injective_take2_FAILED : ∀ n m,
double n = double m →
n = m.
Proof.
intros n m. induction m as [| m' IHm'].
- (* m = O *) simpl. intros eq. destruct n as [| n'] eqn:E.
+ (* n = O *) reflexivity.
+ (* n = S n' *) discriminate eq.
- (* m = S m' *) intros eq. destruct n as [| n'] eqn:E.
+ (* n = O *) discriminate eq.
+ (* n = S n' *) apply f_equal.
(* We are stuck here, just like before. *)
Abort.
double n = double m →
n = m.
Proof.
intros n m. induction m as [| m' IHm'].
- (* m = O *) simpl. intros eq. destruct n as [| n'] eqn:E.
+ (* n = O *) reflexivity.
+ (* n = S n' *) discriminate eq.
- (* m = S m' *) intros eq. destruct n as [| n'] eqn:E.
+ (* n = O *) discriminate eq.
+ (* n = S n' *) apply f_equal.
(* We are stuck here, just like before. *)
Abort.
The problem is that, to do induction on m, we must first introduce n. (And if we simply say induction m without introducing anything first, Coq will automatically introduce n for us!)
What we can do instead is to first introduce all the quantified variables and then re-generalize one or more of them, selectively taking variables out of the context and putting them back at the beginning of the goal. The generalize dependent tactic does this.
Theorem double_injective_take2 : ∀ n m,
double n = double m →
n = m.
Proof.
intros n m.
(* n and m are both in the context *)
generalize dependent n.
(* Now n is back in the goal and we can do induction on
m and get a sufficiently general IH. *)
induction m as [| m' IHm'].
- (* m = O *) simpl. intros n eq. destruct n as [| n'] eqn:E.
+ (* n = O *) reflexivity.
+ (* n = S n' *) discriminate eq.
- (* m = S m' *) intros n eq. destruct n as [| n'] eqn:E.
+ (* n = O *) discriminate eq.
+ (* n = S n' *) apply f_equal.
apply IHm'. injection eq as goal. apply goal. Qed.
double n = double m →
n = m.
Proof.
intros n m.
(* n and m are both in the context *)
generalize dependent n.
(* Now n is back in the goal and we can do induction on
m and get a sufficiently general IH. *)
induction m as [| m' IHm'].
- (* m = O *) simpl. intros n eq. destruct n as [| n'] eqn:E.
+ (* n = O *) reflexivity.
+ (* n = S n' *) discriminate eq.
- (* m = S m' *) intros n eq. destruct n as [| n'] eqn:E.
+ (* n = O *) discriminate eq.
+ (* n = S n' *) apply f_equal.
apply IHm'. injection eq as goal. apply goal. Qed.
Unfolding Definitions
Definition square n := n × n.
... and try to prove a simple fact about square...
Lemma square_mult : ∀ n m, square (n × m) = square n × square m.
Proof.
intros n m.
simpl.
Proof.
intros n m.
simpl.
... we appear to be stuck: simpl doesn't simplify anything, and
since we haven't proved any other facts about square, there is
nothing we can apply or rewrite with.
To make progress, we can manually unfold the definition of square:
unfold square.
Now we have plenty to work with: both sides of the equality are
expressions involving multiplication, and we have lots of facts
about multiplication at our disposal. In particular, we know that
it is commutative and associative, and from these it is not hard
to finish the proof.
rewrite mult_assoc.
assert (H : n × m × n = n × n × m).
{ rewrite mul_comm. apply mult_assoc. }
rewrite H. rewrite mult_assoc. reflexivity.
Qed.
assert (H : n × m × n = n × n × m).
{ rewrite mul_comm. apply mult_assoc. }
rewrite H. rewrite mult_assoc. reflexivity.
Qed.
At this point, some deeper discussion of unfolding and simplification is in order.
Definition foo (x: nat) := 5.
.... then the simpl in the following proof (or the
reflexivity, if we omit the simpl) will unfold foo m to
(fun x ⇒ 5) m and then further simplify this expression to just
5.
Fact silly_fact_1 : ∀ m, foo m + 1 = foo (m + 1) + 1.
Proof.
intros m.
simpl.
reflexivity.
Qed.
Proof.
intros m.
simpl.
reflexivity.
Qed.
But this automatic unfolding is somewhat conservative. For example, if we define a slightly more complicated function involving a pattern match...
Definition bar x :=
match x with
| O ⇒ 5
| S _ ⇒ 5
end.
match x with
| O ⇒ 5
| S _ ⇒ 5
end.
...then the analogous proof will get stuck:
Fact silly_fact_2_FAILED : ∀ m, bar m + 1 = bar (m + 1) + 1.
Proof.
intros m.
simpl. (* Does nothing! *)
Abort.
Proof.
intros m.
simpl. (* Does nothing! *)
Abort.
The reason that simpl doesn't make progress here is that it
notices that, after tentatively unfolding bar m, it is left with
a match whose scrutinee, m, is a variable, so the match cannot
be simplified further. It is not smart enough to notice that the
two branches of the match are identical, so it gives up on
unfolding bar m and leaves it alone.
Similarly, tentatively unfolding bar (m+1) leaves a match
whose scrutinee is a function application (that cannot itself be
simplified, even after unfolding the definition of +), so
simpl leaves it alone.
At this point, there are two ways to make progress. One is to use destruct m to break the proof into two cases, each focusing on a more concrete choice of m (O vs S _). In each case, the match inside of bar can now make progress, and the proof is easy to complete.
Fact silly_fact_2 : ∀ m, bar m + 1 = bar (m + 1) + 1.
Proof.
intros m.
destruct m eqn:E.
- simpl. reflexivity.
- simpl. reflexivity.
Qed.
Proof.
intros m.
destruct m eqn:E.
- simpl. reflexivity.
- simpl. reflexivity.
Qed.
This approach works, but it depends on our recognizing that the
match hidden inside bar is what was preventing us from making
progress.
A more straightforward way forward is to explicitly tell Coq to unfold bar.
Fact silly_fact_2' : ∀ m, bar m + 1 = bar (m + 1) + 1.
Proof.
intros m.
unfold bar.
Proof.
intros m.
unfold bar.
Now it is apparent that we are stuck on the match expressions on
both sides of the =, and we can use destruct to finish the
proof without thinking too hard.
destruct m eqn:E.
- reflexivity.
- reflexivity.
Qed.
- reflexivity.
- reflexivity.
Qed.
Using destruct on Compound Expressions
Definition sillyfun (n : nat) : bool :=
if n =? 3 then false
else if n =? 5 then false
else false.
Theorem sillyfun_false : ∀ (n : nat),
sillyfun n = false.
Proof.
intros n. unfold sillyfun.
destruct (n =? 3) eqn:E1.
- (* n =? 3 = true *) reflexivity.
- (* n =? 3 = false *) destruct (n =? 5) eqn:E2.
+ (* n =? 5 = true *) reflexivity.
+ (* n =? 5 = false *) reflexivity. Qed.
if n =? 3 then false
else if n =? 5 then false
else false.
Theorem sillyfun_false : ∀ (n : nat),
sillyfun n = false.
Proof.
intros n. unfold sillyfun.
destruct (n =? 3) eqn:E1.
- (* n =? 3 = true *) reflexivity.
- (* n =? 3 = false *) destruct (n =? 5) eqn:E2.
+ (* n =? 5 = true *) reflexivity.
+ (* n =? 5 = false *) reflexivity. Qed.
The eqn: part of the destruct tactic is optional; although we've chosen to include it most of the time, for the sake of documentation, it can often be omitted without harm.
Definition sillyfun1 (n : nat) : bool :=
if n =? 3 then true
else if n =? 5 then true
else false.
Theorem sillyfun1_odd_FAILED : ∀ (n : nat),
sillyfun1 n = true →
odd n = true.
Proof.
intros n eq. unfold sillyfun1 in eq.
destruct (n =? 3).
(* stuck... *)
Abort.
if n =? 3 then true
else if n =? 5 then true
else false.
Theorem sillyfun1_odd_FAILED : ∀ (n : nat),
sillyfun1 n = true →
odd n = true.
Proof.
intros n eq. unfold sillyfun1 in eq.
destruct (n =? 3).
(* stuck... *)
Abort.
Theorem sillyfun1_odd : ∀ (n : nat),
sillyfun1 n = true →
odd n = true.
Proof.
intros n eq. unfold sillyfun1 in eq.
destruct (n =? 3) eqn:Heqe3.
- (* e3 = true *) apply eqb_true in Heqe3.
rewrite → Heqe3. reflexivity.
- (* e3 = false *)
destruct (n =? 5) eqn:Heqe5.
+ (* e5 = true *)
apply eqb_true in Heqe5.
rewrite → Heqe5. reflexivity.
+ (* e5 = false *) discriminate eq. Qed.
sillyfun1 n = true →
odd n = true.
Proof.
intros n eq. unfold sillyfun1 in eq.
destruct (n =? 3) eqn:Heqe3.
- (* e3 = true *) apply eqb_true in Heqe3.
rewrite → Heqe3. reflexivity.
- (* e3 = false *)
destruct (n =? 5) eqn:Heqe5.
+ (* e5 = true *)
apply eqb_true in Heqe5.
rewrite → Heqe5. reflexivity.
+ (* e5 = false *) discriminate eq. Qed.